The Role of Topical Brimonidine Tartrate Gel as a Novel Therapeutic Option for Persistent Facial Erythema Associated with Rosacea - Johnson, Andrew William (Dermatol Ther (Heidelb), 2015)
Rosacea is a chronic inflammatory skin condition that commonly presents with persistent facial erythema with or without the coincident presence of flushing, telangiectasias, inflammatory papules or pustules, phymatous changes, or ocular involvement. Patients often present with a constellation of various signs and symptoms of the disease, and an individualized treatment plan should be tailored to a patient’s unique clinical presentation. Previously available medications for rosacea have all targeted the inflammatory erythematous papules and pustules frequently associated with the disease, leaving a therapeutic gap for the common manifestation of persistent facial erythema. Brimonidine tartrate 0.33% gel was approved by the US Food and Drug Administration in August 2013 as the first medication available for the topical treatment of persistent facial erythema associated with rosacea. Brimonidine gel is a highly selective α2-adrenergic receptor agonist with potent vasoconstrictive effects, which leads to significant reduction of persistent facial erythema in the majority of patients when applied once daily. Based on large-scale clinical trials and post-marketing reports, brimonidine gel has maintained a good safety profile with a minority of patients experiencing adverse effects from its use, most of which are cutaneous in nature, mild-to-moderate in degree, occur early after initiation of treatment, often resolve spontaneously with continued use, and generally resolve after discontinuation of use. Among the reported adverse effects, two distinct manifestations of worsened erythema have been described. Brimonidine gel can be integrated into a treatment regimen along with concomitant therapies for facial papules and pustules with no increased risk of adverse events with combination therapy. Education about optimal application methods, setting reasonable expectations for treatment, and minimizing inflammation are important factors for the successful use of brimonidine gel as part of a patient’s overall rosacea treatment regimen. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13555-015-0078-1) contains supplementary material, which is available to authorized users.